Chinese Buddhist Nuns in the Twentieth Century: A Case Study in Wuhan - Yuan Yuan (Journal of Global Buddhism, 2015)
In this paper, through working at the intersection of the works on nationalism and women, and the literature on Buddhist nuns during the Republican period, I aim to take up questions of gender relations in the broader studies of Buddhism and Buddhist modernization. I explore the Buddhist nuns' movement by examining the establishment of various academies for female Buddhists. I also analyze the writings by female Buddhists in the twentieth century. In so doing, I argue that the Buddhist nuns' revival movement fitted into the broader women's liberation discourse and the national modernization project during this time. This paper promises to provide insights into the history of women and nationalism from a Buddhist perspective, and shed light on gender-related issues of modern Chinese Buddhism in the course of China's modernization.